2012
DOI: 10.1107/s0108270112044757
|View full text |Cite
|
Sign up to set email alerts
|

Virtual issue on absolute structure

Abstract: It should come as no surprise, following after the first virtual issue on polymorphism (http://journals.iucr.org/special_issues/2011/polymorphism/), that the Editor has chosen absolute structure (http://journals.iucr.org/special_issues/2012/absolutestructure/) as the topic for this year's effort. The unambiguous determination of absolute structure, particularly where the absolute configuration of an enantiomerically pure chiral molecule is needed, is important not only for synthetic and natural-product chemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Analysis of non-centrosymmetric crystal structures published in Acta Cryst. C in 2007, 2011 and 2012 has shown that even the intensity data of structures with large Friedif stat values may be entirely dominated by random uncertainties and systematic errors (Flack, 2012;Flack et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of non-centrosymmetric crystal structures published in Acta Cryst. C in 2007, 2011 and 2012 has shown that even the intensity data of structures with large Friedif stat values may be entirely dominated by random uncertainties and systematic errors (Flack, 2012;Flack et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On a broader front, it is worth reminding that the standard uncertainty in the Flack parameter, u(x), is the key to its correct interpretation (Flack & Bernardinelli, 2000;Thompson & Watkin, 2009). The use of 2AD plots is thus strongly advised for the validation of absolute-structure determinations (Flack, 2012), together with Flack x and Hooft y parameters. Unfortunately, these plots are not yet used on a routine basis in chemical crystallography.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…However, the primary requirement for its use is to have a properly diffractive crystal, which cannot always be fulfilled. Even with suitable crystals, examples of incorrect absolute configuration determination based on X-ray crystallography alone or crystallographic results needing support by other methods can quite often be found in the literature [ 4 , 5 , 6 , 7 ]. One of the reasons may be more ready crystallization of an unrepresentative component of the bulk material [ 8 ].…”
Section: Introductionmentioning
confidence: 99%